Radio-based Instruction (RBI) Approach to Teaching: The Lived Experiences of Teacher-Broadcasters in the New Normal Education Setting - Teves, Nelson Jr. (Journal of Interdisciplinary Perspectives, 2024)
The COVID-19 pandemic has wreaked havoc on several sectors of society, particularly the education sector. This has caused abrupt shifts in the educational landscape and methodologies, which were manifested through the implementation of several distance learning modalities, such as online, modular, and blended learning. From these modalities, several instructional media and alternatives emerged. One of which was the implementation of Radio-based Instruction (RBI), wherein educational institutions selected teachers to play the role of teacher-broadcasters and deliver instruction on air. However, the implementation has posed many challenges on the part of these teachers. Thus, this study was conducted to investigate the issues faced by teachers in the Bayawan City Division and explore their lived experiences as broadcasters, anchors, and scriptwriters. By adopting Colaizzi's method of data analysis, one emergent theme, “Diverse Challenges Encountered,” was identified, which comprises the following eleven specific problems that serve as subthemes: 1) Novelty of the Method; 2) Difficulties in Learner’s Engagement; 3) Technological Divide; 4) Lack of RBI Knowledge; 5) Scarcity of Resources; 6) Uncertainty in Gauging Student’s Learning; 7) Intricacies in Scriptwriting; 8) Struggles in Content Delivery; 9) Physical and Environmental Barriers; 10) Teacher’s Personal and Psychological Barriers; and 11) Inevitable Time Constraints. The findings revealed that the entirety of the teachers’ lived experience in the implementation of the RBI in the new normal has never been easy and mainly revolves around various challenges encountered in their pedagogical adaptations. They were forced to "adapt rapidly" and experienced several complexities and impediments, implying that educational institutions were not fully equipped and prepared for its implementation during the pandemic. Educational institutions can further investigate ways to address or mitigate these challenges and improve the overall implementation of Radio-based Instruction (RBI) as a viable alternative educational approach in basic education schools.